2002
DOI: 10.1038/sj.onc.1205262
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the interleukin-2/15 receptor β-chain by the EWS–WT1 translocation product

Abstract: EWS ± WT1 is a chimeric transcription factor resulting from fusion of the N-terminal domain of the Ewing sarcoma gene EWS to the three C-terminal zinc ®ngers of the Wilms tumor suppressor WT1. This translocation underlies desmoplastic small round cell tumor (DSRCT), which is noted for the abundance of reactive stroma surrounding islets of tumor cells, suggestive of paracrine signals contributing to tumor cell proliferation. Hybridization to high-density oligonucleotide microarrays can be used to identify targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 52 publications
(46 reference statements)
2
38
0
Order By: Relevance
“…7,9 In addition, the EWS-WT1 chimeric protein has recently been shown to be a potent transcriptional activator of expression of the beta chain of the IL-2/15 receptor in tumor cells and expression of IL2 and IL-15 has been detected in the desmoplastic stroma in desmoplastic small round cell tumors. 13 The prominent stromal reaction might also provide a paracrine signal to neoplastic cell proliferation in these tumors. 13 Bone morphogenic proteins (BMP) are members of the TGF-b superfamily and have a complex role in regulating cell growth and differentiation including bone formation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,9 In addition, the EWS-WT1 chimeric protein has recently been shown to be a potent transcriptional activator of expression of the beta chain of the IL-2/15 receptor in tumor cells and expression of IL2 and IL-15 has been detected in the desmoplastic stroma in desmoplastic small round cell tumors. 13 The prominent stromal reaction might also provide a paracrine signal to neoplastic cell proliferation in these tumors. 13 Bone morphogenic proteins (BMP) are members of the TGF-b superfamily and have a complex role in regulating cell growth and differentiation including bone formation.…”
mentioning
confidence: 99%
“…13 The prominent stromal reaction might also provide a paracrine signal to neoplastic cell proliferation in these tumors. 13 Bone morphogenic proteins (BMP) are members of the TGF-b superfamily and have a complex role in regulating cell growth and differentiation including bone formation. 14 Overexpression of BMP4 has been found in patients with fibrodysplasia ossificans progressiva and various bone and soft-tissue sarcomas.…”
mentioning
confidence: 99%
“…Interestingly, the two isoforms differ in their oncogenic activities as only the EÀKTS, but not EþKTS, has the potential to transform NIH3T3 cells in vitro (17). Therefore, the majority of studies have focused on identifying the target genes of EÀKTS (18)(19)(20)(21)(22), whereas only two genes have been identified as direct targets of EþKTS (22,23). These studies also revealed different DNA recognition sequences of each isoform: EÀKTS binds to either a GC-rich, 5 0 -GXG(T/G)GGGXG-3 0 (X is any base; refs.…”
Section: Introductionmentioning
confidence: 99%
“…The b-subunit, which is shared by IL-3R, granulocytemacrophage colony-stimulating factor receptor and IL-5R, is constitutively activated by extracellular truncation [24,25]. Similarly, there are genomic alterations that increase IL-2R expression in many tumor cells [26,27]. There are no reports, however, of structural alterations leading to cytokine-independent activation of IL-2R.…”
Section: Introductionmentioning
confidence: 98%